Comparative study of size exclusion chromatography for isolation of small extracellular vesicle from cell-conditioned media, plasma, urine, and saliva - Contreras, Hector; Alarcón-Zapata, Pedro; Nova-Lamperti, Estefania; Ormazabal, Valeska; Varas-Godoy, Manuel; Salomon, Carlos; Zuniga, Felipe A. (Frontiers in Nanotechnology, 2023)
Extracellular vesicles (EVs) are secreted from all types of cells and are involved in the trafficking of proteins, metabolites, and genetic material from cell to cell. According to their biogenesis and physical properties, EVs are often classified as small EVs (including exosomes) or large EVs, and large oncosomes. A variety of methods are used for isolated EVs; however, they have several limitations, including vesicle deformation, reduced particle yield, and co-isolate protein contaminants. Here we present an optimized fast and low-cost methodology to isolate small EVs (30 to 150 nm) from biological fluids comparing two SEC stationary phases, G200/120 and G200/140 columns. The optimization parameters considered were a) the selection of the stationary phase, b) the eluate volume per fraction, and c) the selection of the enriched 30 to 150 nm EVs-fractions. The efficiency and separation profile of each UF/SEC fraction was evaluated by NTA, flow cytometry, total protein quantification, and Western blot. The results suggest that both columns can isolate predominantly small EVs with low protein contaminants from plasma, urine, saliva, and HEK293-derived EV from collection medium. Column G200/40 offers a more homogeneous enrichment of vesicles between 30 and 150 nm than G200/120 [76.1 ± 4.4% with an average size of 85.9 ± 3.6 nm (Mode: 72.8 nm)] in the EV collection medium. The enrichment, estimated as the vesicle-to-protein ratio, was 1.3 x 1010 particles/mg protein for G200/40, obtaining a more significant EVs enrichment compared to G200/120. The optimized method delivers 0.8 mL of an EVs-enriched-outcome, taking only 30 mins per sample. Using plasma, the enrichment of small EVs from the optimized method was 70.5 ± 0.18%, with an average size of 119.4 ± 6.9 nm (Mode: 120.3 nm), and the enrichment of the vesicle isolation was 4.8 x 1011 particles/mg protein. The average size of urine and saliva EVs samples was 147.5 ± 3.4 and 111.9 ± 2.5 nm, respectively. All the small EVs isolated from the samples exhibit the characteristic cup-shaped morphology observed by Transmission electron microscopy. This study suggests that the combination of methods is a robust, fast, and improved strategy for isolating small EVs.